The Role of Artificial Intelligence (AI) in Online Media Routines of TvOne AI Publications - Norhusin, David; Harliantara, Harliantara; Panuju, Redi; Abror, Dhimam; Maella, Nurannafi Farni Syam (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research investigates the use of artificial intelligence (AI) technology in producing news content on TVOne, focusing on the presence of Karni Ilyas as an AI presenter in the